Practical skills in forensic science - Langford, Alan; Dean, John; Reed, Rob; Holmes, David (Harlow, England : Pearson Education Limited, 2010)
Practical Skills in Forensic Science is designed specifically to support and develop the complete range of practical skills which are essential to success in Forensic Science courses. This range of skills includes work in practicals and laboratory sessions, and also relates to projects, study skills and assessments, exam revision, time management, and even how to put together a CV. The authors provide an updated concise and user-friendly guide, which will help students to focus on how to perform as effectively as possible in their course
Includes bibliographical references and index.
Keywords: Forensic sciences